2011
DOI: 10.3852/10-121
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic and aqueous extracts derived from Australian fungi inhibit cancer cell growth in vitro

Abstract: Fifteen Australian macrofungi were investigated for cytotoxic activity. Ethanol, cold and hot water extracts of each species were screened for cytotoxic activity against normal mouse fibroblast cells (NIH/3T3), healthy human epithelial kidney cells (HEK-293), four cancer cell lines, gastric adenocarcinoma cells (AGS), two mammary gland adenocarcinoma cells (MDA-MB-231, MCF7) and colorectal adenocarcinoma cells (HT-29) with a validated MTT assay. Most extracts derived from Omphalotus nidiformis, Cordyceps crans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…Meanwhile, K562 cells turned out to be much more sensitive to PFCF than PBMC cells (Figure 2(b)). This is partly in agreement with Beattie et al’s report; 15 their results indicated that 15 Australian fungi species showed low or no cytotoxic activity against human healthy cells and some had significant ( Omphalotus nidiformis , Cordyceps Cranstounii , and Cordyceps gunnii ) and selective ( Xerula mundroola , Leratiomyces ceres , and Hypholoma fasciculare ) activity against cancer cells. The data suggest that the P. fomentarius might be of great potential in cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, K562 cells turned out to be much more sensitive to PFCF than PBMC cells (Figure 2(b)). This is partly in agreement with Beattie et al’s report; 15 their results indicated that 15 Australian fungi species showed low or no cytotoxic activity against human healthy cells and some had significant ( Omphalotus nidiformis , Cordyceps Cranstounii , and Cordyceps gunnii ) and selective ( Xerula mundroola , Leratiomyces ceres , and Hypholoma fasciculare ) activity against cancer cells. The data suggest that the P. fomentarius might be of great potential in cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that these novel species contain or produce compounds and secondary metabolites that are valuable in the treatment of disease and other medical ailments (e.g., cancer, statin production) or have industrial uses as enzymes (Østergaard & Olsen, 2010; Beattie & Ulrich, 2011). Some fungi may even have utility in the bioremediation of industrial waste and oil spills (Atalla et al, 2010; Garzoli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic activity of PFPE on S180 cells was measured with the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Healthy human epithelial kidney cells (HEK-293) were used as normal cells [31] , [32] by contrast to examine the cytotoxic effect of the PFPE. Briefly, the control or PFPE-loading cells at the density of 5×10 4 cells/ml (100 µl) were seeded in 96 well culture plates, and cell viability after different incubations (24 and 48 h) was determined by adding 10 µl of MTT solution (5 mg/ml in PBS) and the mixture was incubated for an additional 4 h at 37°C in a CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%